Potential of The Hydroponic Vegetables to Support Food Security in Defense Management Perspective - Fanema Gabrieli; Hikmat Zakky Almubaroq (Faculty of Social Science, Universitas Negeri Padang, 2021)
In order to support food security, it would be better if the food priority is not only limited to rice, but also supports and optimizes the diversity of technology-based products such as hydroponic vegetables. In Medan City, the hydroponic market was still relatively small. This was seen from the unavailability of hydroponic products sold in various shopping canters. The objective of the study was to identify the internal and external factors in increasing the management of hydroponic vegetables and to formulate the development strategy of hydroponic vegetables in Medan, in order to support food security. The research used a descriptive analytic method by using SWOT, defence management, and food security theory. The samples were taken by using snowball sampling technique. Respondents consisted of several farmers, members of the Hydroponic Community in Medan City (HCM), consumers, officials of the Food Security Agency (BKP) of Medan, and a counsellor from the Agriculture Agency. SWOT matrix analysis of internal and external factors of the Food Security Agency (BKP), Medan showed that the hydroponic vegetables farming development strategy was in quadrant one. The recommended strategy was aggressive strategy which was focused on using strength and opportunity owned by the Food Security Agency (BKP) in order to cope with weakness and threat